Peran Moderator Customer Value dan Destination Satisfaction pada Hubungan Core Tourism Resources terhadap Destination Image: Studi Kasus Destinasi Desa Wisata - Amir, Muhammad; Dzulfadeln, Prawira Aditiya; Ardiansyah, Ardiansyah (Al-Buhuts, 2024)
This study aims to examine the effect of core tourism resources on destination image and the moderating impact of customer value and destination satisfaction on the relationship between core tourism resources and destination image. Quantitative research approach with partial least squares structural equation modeling (PLS-SEM) analysis. Data were collected from 245 tourists from several tourist attractions in Gowa Regency. The results showed that natural resources and heritage resources have a positive effect on destination image. However, created resources do not affect destination image. Customer value can moderate the effect of Natural resources and created resources on destination image. However, customer value is unable to moderate the effect of heritage resources on destination image. Destination satisfaction is able to moderate the effect of natural resources and created resources on destination image. However, destination satisfaction does not moderate the effect of heritage resources on destination image